Caspases and therapeutic potential of caspase inhibitors in moderate–severe SARS‐CoV‐2 infection and long COVID. Issue 1 (2nd June 2021) - Plassmeyer, Matthew; Alpan, Oral; Corley, Michael J.; Premeaux, Thomas A.; Lillard, Kimberleigh; Coatney, Paige; Vaziri, Tina; Michalsky, Suzan; Pang, Alina P. S.; Bukhari, Zaheer; Yeung, Stephen T.; Evering, Teresa H.; et al.
Abstract: Background: COVID‐19 can present with lymphopenia and extraordinary complex multiorgan pathologies that can trigger long‐term sequela. Aims: Given that inflammasome products, like caspase‐1, play a role in the pathophysiology of a number of co‐morbid conditions, we investigated caspases across the spectrum of COVID‐19 disease. Materials & Methods: We assessed transcriptional states of multiple caspases and using flow cytometry, the expression of active caspase‐1 in blood cells from COVID‐19 patients in acute and convalescent stages of disease. Non‐COVID‐19 subject presenting with various comorbid conditions served as controls. Results: Single‐cell RNA‐seq data of immune cells from COVID‐19 patients showed a distinct caspase expression pattern in T cells, neutrophils, dendritic cells, and eosinophils compared with controls. Caspase‐1 was upregulated in CD4+ T‐cells from hospitalized COVID‐19 patients compared with unexposed controls. Post‐COVID‐19 patients with lingering symptoms (long‐haulers) also showed upregulated caspase‐1activity in CD4+ T‐cells that ex vivo was attenuated with a select pan‐caspase inhibitor. We observed elevated caspase‐3/7levels in red blood cells from COVID‐19 patients compared with controls that was reduced following caspase inhibition. Discussion: Our preliminary results suggest an exuberant caspase response in COVID‐19 that may facilitate immune‐related pathological processes leading to severe outcomes. Further clinical correlations of caspase expression in different stages of COVID‐19 will be needed. Conclusion: Pan‐caspase inhibition could emerge as a therapeutic strategy to ameliorate or prevent severe COVID‐19. Abstract : This study assesses transcriptional states of multiple caspases and the expression of active caspase‐1 in blood cells from COVID‐19 patients in acute and convalescent stages of disease. Elevated caspase‐3/7 levels in red blood cells is observed in COVID‐19 patients compared to controls. Post‐COVID‐19 patients with lingering symptoms show up‐regulated caspase‐1 activity in CD4+ T‐cells that is attenuated ex vivo with a select pan‐caspase inhibitor. An exuberant caspase response in COVID‐19 that may facilitate immune‐related pathological processes leading to severe outcomes. Abbreviations: APC, antigen‐presenting cell; COVID‐19, coronavirus disease 2019; ICU, intensive care unit; PBMC, peripheral blood mononuclear cell; RBC, red blood cell; SARS‐CoV‐2, severe acute respiratory syndrome coronavirus 2